Losing twice harms of indifference in the Supreme Court - Calhoun, Emily M. (New York ; Oxford : Oxford University Press, 2011)
Constitutional 'losers' represent a thorny and longstanding problem in American constitutional law. Here, Emily Calhoun draws upon conflict resolution theory, political theory, and Habermasian discourse theory to argue that in such cases, the Court must work harder to avoid inflicting unnecessary harm on Constitutional losers.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: United States. -- Supreme Court -- Decision making; Equality before the law -- United States; Apathy